DESPERDÍCIO DA ÁGUA: SOLUÇÕES APLICÁVEIS NO AMBIENTE ESCOLAR - Jossany Almeida Brito, Mayra; Pereira de Oliveira, Rosivaldo; da Costa Brito, Clecina; Ferreira Lima, Edmar; Cristhina Aragão Pereira, Cynara (Revista Form@re - Parfor/UFPI, 2026)
.